Pengaruh Self-regulated Learning dan Adversity Quotient terhadap Prestasi Akademik Mahasiswa Pendidikan Ekonomi UNS - Adi Saputro, Bayu; Indriayu, Mintasih (FKIP Unswagati, 2025)
This research investigates the effect of self-regulated learning and adversity quotient on the academic achievement of Economics Education students at Sebelas Maret University (UNS). Utilizing a descriptive quantitative approach, the study involved 189 students from the 2022–2024 cohorts of the Economics Education Study Program. The sample was selected using a proportional random sampling technique, with the inclusion criteria being active participation in learning activities and possession of a Grade Point Average (GPA). Instrument validity was assessed using Pearson’s product-moment correlation, while reliability was measured through Cronbach’s alpha. Data analysis included descriptive statistics, classical assumption testing, and simple linear regression, assisted by SPSS Statistics version 26. The findings indicate that: (1) self-regulated learning exerts a positive and significant impact on academic achievement, evidenced by a t-value of 10.832 exceeding the t-table value of 1.973, with a significance level of 0.000 < 0.05; and (2) adversity quotient also shows a positive and significant influence on academic achievement, with a t-value of 10.175 surpassing the t-table value of 1.973 and a significance level of 0.000 < 0.05. Keywords: self-regulated learning, adversity quotient, academic achievement.